PELATIHAN BUDIDAYA IKAN TERINTEGRASI PADA KELOMPOK ISTRI NELAYAN GAMPONG RANTO PANYANG TIMUR - Sufal Diansyah; Yusran Ibrahim; Dini Islama; Zulfadhli Zulfadhli; Roni Arif Munandar; Hafif Syahputra (Universitas Teuku Umar, 2021)
Income of fishers in West Aceh District usually fluctuating, indicate by the small of number of catches of fisherman. Another thing that has a negative impact on the economy fishermens households is the Covid-19 pandemic. Limited land is a problem for fishermen’s families, previously fishermen’s wives drying salted fish to increase their income. One of the tips is to apply fish cultivation technology on limited land with the Integrated Multi-Trophic Aquaculture (IMTA) system. The purpose of this activity is to provide knowledge to a group of fishermen’s wives about fish farming based on the IMTA system. The method used is the socialization of IMTA system fish farming, IMTA system fish pond construction training, production management guidance, training on production performance analysis and marketing strategy, monitoring and evaluation. Integrated fish cultivation training activities for groups of fishermen’s wives received positive support and response from group partners. This activity is very beneficial for houswives because they get new skills to increase economic income. This program is a solution for fishermen’s families during uncertain economic conditions due to the Covid-19 pandemic. This group activity will be an inspiration and model for other fishermen’s wives to do fish farming in limited land and water sources.